An M2-polarized macrophage microenvironment drives leukemogenesis and poor prognosis in acute myeloid leukemia - Weinhäuser, Isabel (2021)
While it is increasingly becoming clear that cancers are a symbiosis of diverse cell types and tumor clones, the tumor supportive microenvironment (TSM) in acute myeloid leukemias (AML) remains poorly understood. Here, we uncover that patients with the poorest prognosis harbor an M2-polarized macrophage compartment. Coculture of leukemic blasts on M2 macrophages promotes cell survival and drug resistance. Intrabone marrow co-injection of M2- macrophages induces fatal leukemia of acute promyelocytic leukemia blasts, which are otherwise poor grafters. Even a short-term two-day in vitro exposure to M2 macrophages can \"train\" leukemic blasts after which cells are protected against phagocytosis, display increased mitochondrial metabolism and in vivo homing, resulting in full-blown leukemia. We developed an M2-based biomarker panel that outperforms currently used AML prognosis predictors. Our study provides insight into the mechanisms by which the TSM contributes to aggressive leukemia development and provides alternatives for effective targeting strategies.